The role of educational systems in entrepreneurship with the impact of e-learning - Zohreh Riazi (پژوهش در نظام‌های آموزشی, 2018)
Educational systems that have contributed to the competitive economy have been accompanied by rapid and rapid changes in internationalization, and their characteristics are the transition from the industrial community to the education-based information society and the shift in the national economy's rates to the global economy. In accredited educational systems, entrepreneurship is referred to as an economic development engine. The entry of educational and information technology and the Internet into trade exchanges, while facilitating these exchanges, has greatly reduced the amount of costs. For this reason, most of the world's educational systems are looking for faster and more serious entry into the markets of educational and electronic exchanges through the Internet to their clients. The purpose of this study was to investigate the role of educational systems in entrepreneurship with regard to the impact of e-learning. This research has been done by descriptive-survey method. The statistical population of the study was 260 people. A questionnaire of 38 questions was distributed among the staff. The reliability of the questionnaire was calculated using Cronbach's alpha (0.75). The collected data were analyzed by descriptive and inferential statistics in the form of Pearson correlation test using spss software. The findings of this study showed that factors such as organizational, economic, e-learning features have a significant role in developing small enterprises based on e-learning in Shiraz.